Heat transport in micro and nanoscale thin films - Yilbas, B. S.; Bin Mansoor, Saad; Ali, Haider (Micro & Nano Technologies Series, 2018)
Heat Transport in Micro- and Nanoscale Thin Films presents aspects and applications of the principle methods of heat transport in relation to nanoscale films. Small-scale parts and thin films are widely used in the electronics industry. However, the drastic change in the thermal conductivity with reducing device size and film thickness modifies the energy transport by heat-carrying phonons in the film. Energy transfer in small-sized devices and thin films deviate from the classical diffusion to radiative transport. This book deals with micro/nano scale heat transfer in small scale devices and the thin films, including interface properties of cross-plane transport. The book fills the gap between applications of the physical fundamentals and energy transport at the micro- and nano scale, which will be valuable for academics, researchers and students in the fields of materials science and energy transport.